FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PERSALINAN NORMAL DI KLINIK BERSALIN BUDI MULIA MEDIKA PALEMBANG PADA TAHUN 2011 - Nurdjani Nurdjani (STIKes Budi Mulia Sriwijaya, 2012)
ABSTRACT Childbirth is a process in which the baby, placenta and amniotic membranes out of the mother's uterus at full term pregnancy after 37 weeks) without any complications.According to the Word Health Organization (WHO) estimates that more than 585 000 women die annually during pregnancy or childbirth. Indonesia Demographic Health Survey (IDHS) in 2008 states the maternal mortality rate (MMR) at delivery was 228 per 100,000 live births and infant mortality rate (IMR) 34 per 1,000 live births. The purpose of this study are known factors associated with normal delivery at the Budi Mulia Clinic in Palembang 2011. This study uses analytic survey with cross sectional approach. The population in this study were all mothers in the maternity Maternity Budi Mulia Clinic in Palembang May 2011. Sampling was carried out on non-randomized study with the technique of